Analisis Resepsi Audien pada Konten Storytelling Nadhifa Allya Tsana di Podcast Rintik Sedu - Ridzky Ananda, Ridzky; Prismarini Nurdiarti, Rosalia (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2024)
This research was conducted to analyze audience reception of Nadhifa Allya Tsana's storytelling content on the Rintik Sedu podcast via social media on the Instagram account @rintiksedu. This research aims to be a means of information and also a reference in adding to developments in the field of communication science studies. In this research the author uses qualitative research with a descriptive analysis approach. The data collection method uses interviews. The results of this research conclude that the audience's reception of Rintik Sedu's storytelling content varies and is very dependent on the audience's social context. Reception theory opens a new perspective to view audiences and the dynamics of their media decoding process.